Relationship between blood levels of heavy metals and lung function based on the Korean National Health and Nutrition Examination Survey IV–V - Leem AY; Kim SK; Chang J; Kang YA; Kim YS; Park MS; Kim SY; Kim EY; Chung KS; Jung JY (International Journal of COPD, 2015)
Ah Young Leem, Se Kyu Kim, Joon Chang, Young Ae Kang, Young Sam Kim, Moo Suk Park, Song Yee Kim, Eun Young Kim, Kyung Soo Chung, Ji Ye Jung Division of Pulmonology, Department of Internal Medicine, Institute of Chest Disease, Severance Hospital, Yonsei University College of Medicine, Seoul, Republic of Korea Background: Heavy metal exposure may contribute to inflammation in the lungs via increased oxidative stress, resulting in tissue destruction and obstructive lung function (OLF). In this study, we evaluated the relationship between lead and cadmium levels in blood, and lung function in the Korean population.Methods: Pooled cross-sectional data from 5,972 subjects who participated in the Korean National Health and Nutrition Examination Survey 2008–2012 were used for this study. OLF was defined as forced expiratory volume in 1 second/forced vital capacity (FEV1/FVC) <0.7. Graphite-furnace atomic absorption spectrometry was used to measure levels of lead and cadmium in blood.Results: Adjusted means for age, sex, body mass index, and smoking status in blood lead and cadmium levels were increased with age and were higher in men and current smokers. The FEV1/FVC ratio was lower in the highest quartile group of lead (78.4% vs 79.0%; P=0.025) and cadmium (78.3% vs 79.2%; P<0.001) concentrations, compared with those in the lowest quartile groups. Multiple linear regression demonstrated an inverse relationship between the FEV1/FVC ratio and concentrations of lead (estimated -0.002; P=0.007) and cadmium (estimated -0.005; P=0.001). Of the 5,972 subjects, 674 (11.3%) were classified into the OLF group. Among current smokers, the risk of OLF was higher in subjects in the highest quartile group of cadmium concentration than in those in the lowest quartile group (odds ratio 1.94; 95% confidence interval 1.06–3.57).Conclusion: We demonstrated a significant association between the FEV1/FVC ratio and blood concentrations of lead and cadmium in the Korean population. The risk for OLF was elevated with increasing concentrations of cadmium among current smokers. Keywords: lead, cadmium, pulmonary function, obstructive lung disease